Analysis Of Differences In The Quality Of Beef Rendang Using Roasted Coconut (Ambu-Ambu) And Not Using Roasted Coconut (Ambu-Ambu) - Maryetta, Mila; Elida, Elida (Universitas Negeri Padang, 2022)
This research is motivated by the differences in randang in each region, ranging from the materials to be used, as well as the processing techniques used in making the rendang. Based on some published literature related to rendang research, there are differences in the additional ingredients for meat rendang, where there are areas that use roasted coconut (ambu-ambu), and some do not use roasted coconut (ambu-ambu) in the processing of meat rendang. The one that uses roasted (ambu-ambu) as an additional ingredient is found in Nagari Ujung Gading, Lembah Melintang District, West Pasaman Regency. The purpose of this study was to analyze the differences in the quality of meat rendang using roasted coconut (ambu-ambu) and not using roasted coconut (ambu-ambu), including, shape, color, aroma, texture and taste of meat rendang.The type of research conducted is quantitative research with experimental methods and completely randomized design (CRD). Data were obtained from 5 expert panelists, using the organoleptic test format, then the data were analyzed by t-test.The results of this study indicate that the highest value is found in meat rendang using roasted coconut (ambu-ambu) where the quality of the shape of the meat (2.8), the color of the meat (3.4), the color of the spices (3.4), the aroma of the randang ( 3,07), meat texture (3,47), seasoning texture (2,8), randang meat taste (3,47,) and randang seasoning flavor (3,27). Based on the hypothesis test that has been obtained, it shows that there is no significant difference in the quality of the meat shape, meat color, seasoning color, randang aroma, meat texture, seasoning texture, and randang meat taste which indicates Ho is accepted and Ha is rejected but there are significant differences in the quality of the taste of the meat rendang seasoning using roasted coconut (ambu-ambu) which indicates Ha is accepted and Ho is rejected.